Overexpression of Galectin 3 in Pancreatic β Cells Amplifies β-Cell Apoptosis and Islet Inflammation in Type-2 Diabetes in Mice - Petrovic, Ivica; Pejnovic, Nada; Ljujic, Biljana; Pavlovic, Sladjana; Miletic Kovacevic, Marina; Jeftic, Ilija; Djukic, Aleksandar; Draginic, Nevena; Andjic, Marijana; Arsenijevic, Nebojsa; Lukic, Miodrag L.; Jovicic, Nemanja (Frontiers in Endocrinology, 2020)
Aims/hypothesis: Galectin 3 appears to have proinflammatory role in several inflammatory and autoimmune diseases. Also, there is evidence that galectin 3 plays a role in both, type 1 and type 2 diabetes. During obesity hematopoetic cells-derived galectin 3 induces insulin resistence. While the role of galectin 3 expressed in islet invading immune cells in both type 1 and type 2 diabetes has been studied, the importance of expression of this molecule on the target pancreatic beta cells is not defined. Methods: To clarify the role of galectin 3 expression in beta cells during obesity-induced diabetogenesis, we developed transgenic mice selectively overexpressing galectin 3 in beta cells, and tested their suceptibility to obesity induced type 2 diabetes. Obesity was induced with 16 weeks high fat diet regime. Pancreatic beta cells were tested for susceptibility to apoptosis induced by non-esterified fatty acids and cytokines as well as parameters of oxidative stress. Results: Our results demonstrated that overexpression of galectin 3 increases beta cells apoptosis in HFD conditions and increases the percentage of proinflammatory F4/80+ macrophages in islets that express galectin 3 and TLR4. In isolated islets, we have shown that galectin 3 overexpression increases cytokine and palmitate-triggered beta cells apoptosis and also increases NO2- induced oxidative stress of beta cells. Also, in pancreatic lymph nodes, macrophages were shifted towards proinflammatory TNF-α producing phenotype. Conclusions/interpretation: By complementary approach in vivo and in vitro, we have shown that galectin 3 overexpression facilitates beta cell damage, enhances cytokine and palmitate-triggered beta cells apoptosis and also increases NO2- induced oxidative stress in beta cells. Further, the results suggest that increased expression of galectin 3 in the pancreatic beta cells affects the metabolism of glucose and glycoregulation in mice on HFD, affecting the fasting glycemic values, as well as glycemia after glucose loading.